The Effect of Hand Anthropometric Variables on Grip Strength in Grip Elite Athletes and Non-Athletes - Tufan Ulcay; Kazım Kaya; Ahmet Uzun; Ersan Kara; Burcu Kamaşak; Naime Meric Konar (Türk Spor ve Egzersiz Dergisi)
In this study, we aimed to determine the anthropometric variables that affect grip strength and to investigate how and to what extent these variables change grip strength in elite athletes and non-athletes. Totally, 74 subjects aged between 18 and 27 participated in this study in two groups including: elite athletes (n=32), and non-athletes (n=42). In our study, 26 hand anthropometric variables were measured on each subject’s dominant hand. The selection of the anthropometric parameters was limited only to those that are considered to have an association with handgrip strength. Independent t-test or Mann-Whitney U Test was applied for group comparison. Stepwise multiple linear regression analysis was utilized and Backward selection procedure was also performed to identify the relationship between handgrip strength and anthropometric measurements. Results revealed that some anthropometric measurements of hand significantly higher in elite athlete group than non-athlete group in males and females (p lt;0.05). In conclusion, we found that some hand anthropometric parameters are different in the grip sports and non-athletes, but we cannot exactly determine whether specific sport activities affect these differences or the inherent characteristics of athletes lead them to these sports. Also the handgrip strength of hand related athletes was more than that of non-athletes. This may be because of hand anthropometric parameters. Actually, good positive correlation between handgrip strengths and anthropometric characteristics of hand in grip athletes showed the effect of hand anthropometry on handgrip strength in athletes who use their hands for grasping a ball or opponent.